2020
DOI: 10.1167/iovs.61.6.30
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Activation After Inhibition Restores Trabecular Meshwork Cells Toward a Normal Phenotype

Abstract: Wnt is a spatiotemporally regulated signaling pathway whose inhibition is associated with glaucoma, elevated intraocular pressure (IOP), and cell stiffening. Whether such changes are permanent or may be reversed is unclear. Here, we determine if activation of Wnt pathway after inhibition reverses the pathologic phenotype. METHODS. Primary human trabecular meshwork (hTM) cells from nonglaucomatous donors were cultured for 12 days in the absence or presence of Wnt modulators: (i) LGK974 (Porcn inhibitor, 10 μM);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 92 publications
2
30
0
1
Order By: Relevance
“…Finally, because 10% XCDM stiffened hTM cells in correlation with inactivating the Wnt pathway, and antagonism of this pathway had previously been implicated in hTM cell stiffening, 50 we explored whether activation of this pathway could rescue hTM cells from 10% XCDM-induced stiffening. Intriguingly, canonical Wnt pathway activation (via inhibition of GSK3β) abrogated 10% XCDM-dependent stiffening of hTM cells, consistent with a recent study from our group, 80 where canonical Wnt pathway activation reversed the pro-fibrotic effects (for instance, cell stiffening) of Wnt pathway inhibition in hTM cells seeded on glass/plastic substrates.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, because 10% XCDM stiffened hTM cells in correlation with inactivating the Wnt pathway, and antagonism of this pathway had previously been implicated in hTM cell stiffening, 50 we explored whether activation of this pathway could rescue hTM cells from 10% XCDM-induced stiffening. Intriguingly, canonical Wnt pathway activation (via inhibition of GSK3β) abrogated 10% XCDM-dependent stiffening of hTM cells, consistent with a recent study from our group, 80 where canonical Wnt pathway activation reversed the pro-fibrotic effects (for instance, cell stiffening) of Wnt pathway inhibition in hTM cells seeded on glass/plastic substrates.…”
Section: Discussionsupporting
confidence: 90%
“… 71 , 77 Correspondingly, in hTM cells cultured on 10% XCDM, at an early time point (24 hours), we observed reduced expression of critical target genes and proteins of Wnt/β-catenin pathway like Axin2, CD44, total fibronectin, and fibronectin EDA isoform. Whereas Wnt antagonism has been shown to be implicated in POAG, elevated intraocular pressure, 49 and cell stiffening, 50 activation of this pathway may have a therapeutic benefit by inhibiting transforming growth factor beta 2 (TGFβ2) signaling pathway, 69 a well-established profibrotic pathway in POAG, 78 , 79 reducing the expression of profibrotic ECM proteins, 70 , 80 and/or regulating cell-cell contacts via K-cadherin expression. 51 Regarding the latter, cadherins’ role in maintaining cell-cell adhesion is partly to allow for their mechanosensitive/mechanotransduction function, 81 83 together with formation of gap junctions to enhance cell-cell communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this mouse model, a great reduction of ocular hypertension with concomitant Wnt3a expression was observed, suggesting activation of canonical Wnt signaling could be a potential therapeutic strategy for GC-induced ocular hypertension prevention and/or treatment. Recently, Dhamodaran et al 55 demonstrated in vitro that another GSK3b inhibitor softens primary TM cells as well as inhibits the expression of ECM, cross-linkers of ECM, and inhibitors of matrix metalloproteinases. Although the changes in genes involved in ECM remodeling were not determined in that study, their roles in ocular hypertension prevention were inferred in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cotreatment with a small-molecule WNT pathway activator can downregulate sFRP1-induced OHT in mouse eyes. The activation of WNT/β-catenin pathway in the TM using lithium chloride decreases the production of some ECM and matricellular proteins [ 125 , 126 ]. WNT/β-catenin signaling and K-cadherin expression are major for the control of IOP, and the downregulation of this pathway leads to IOP elevation in glaucoma [ 127 ].…”
Section: Wnt/β-catenin Pathway In Glaucomamentioning
confidence: 99%